Nothing but the truth a documentary novel - Avi 1937- (New York Orchard Books, 1991)
A ninth-grader's suspension for singing "The Star-Spangled Banner" during homeroom becomes a national news story.
"A Richard Jackson book."
Keywords: High schools -- Fiction; Schools -- Fiction